Marketingovo-produktová strategie společnosti Mediahost na domácím trhu - Šiška, Jakub (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Tato diplomová práce navrhuje marketingovou strategii pro firmu Mediahost podnikající v oboru hostingových služeb. Strategie je zaměřená na slovenský, tedy pro společnost domácí trh. Strategie je podložená příslušnou analýzou. V tomhle případe byl použit “seven Cs” model, taktéž znám jako Compass model, a to spolu se SWOT analýzou. Strategie navrhuje komplexní marketingovou strategii odrážející současné prostředí hostingového trhu.

Diploma thesis is proposing marketing strategy for Mediahost company, which is small enterprise operating in web hosting business. Strategy is designed for Slovak market, home market of the company. Strategy is supported by appropriate analysis. In this case, seven Cs framework, also known as Compass model, has been used along with SWOT analysis. Strategy proposes comprehensive marketing strategy reflecting contemporary environment of hosting business.
Marketing-Product Strategy at Mediahost Company within The Home Market
Keywords: marketingová strategie; analýza trhu; Compass model; Seven Cs model; SWOT; IT; web; hosting; doména; zákaznická podpora; podíl na trhu; Slovensko; marketing strategy; market analysis; Compass model; Seven Cs model; SWOT; IT; web; hosting; domain; customer support; market share; Slovakia